(3QhVI GdCNHGQ hcfhR GdCSQGQ hfcJ GddBKGQs - (3CHh eMeO jhSa Hf eMeO Hf GdMajU, GdMLhQjs
(3ChdgG (B:s
(3hai gPG GdLRA GdNHQ Yf NdaGA Hfi CejI hCfSGHge hUaGJge heOI edcge , hef NQL Ydgje ai SdWGfge ef GdSQGI hGdYdhjI s
(3BNQgG (B:s
(3BNQg ef (B" (3HGH ai hUa GdLfI (B" (3bhdg (B: (3dPgdJ faSc ShbkG EdjgG hdJYLdJ ef eLdSi gPG Edi eLGhQI Cgd GdbHhQ ZSJYLGdkG HgG Je GdLRA GdQGHY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdLRA GdQGHY ef fSNI CNQis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf Ydi GdCchY GdNGUI s
Keywords: (3GdJGQjNs